2015
DOI: 10.1380/ejssnt.2015.469
|View full text |Cite
|
Sign up to set email alerts
|

Growth of GaAsBi/GaAs Multi Quantum Wells on (100) GaAs Substrates by Molecular Beam Epitaxy

Abstract: Multi-quantum wells (MQWs) consisting of 3 or 3.5 pairs of nominally 8.8-nm-thick GaAs layers and 5.6-nmthick GaAs0.97Bi0.03 were grown by molecular beam epitaxy with varying the growth temperature of GaAs layers, TGaAs, and keeping the growth temperature of the GaAsBi layers at 350• C and their Bi compositional structure and optical properties were investigated. Analysis of x-ray diffraction spectra reveals that 67% of the total Bi atoms supplied during growth of a single GaAsBi layer were segregated on the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…Note that Bi atoms tend to segregate during growth of GaAsBi and will then incorporate into the (Al)GaAs barrier, therefore increasing the total strain energy and altering the total thickness of the active layer [23]. Here we demonstrate that the growth of GaAsBi/ GaAs MQWs using a two-substrate-temperature (TST) technique during MBE growth, where the GaAs layer is grown at a higher temperature than the GaAsBi layer to sig-nificantlyreduce Bi segregation [22,24]. The material grown using the TST approach is of high optical device quality as demonstrated by the successful realization of p-i-n diode structures based on GaAs 0.96 Bi 0.04 /GaAs MQWs with RT EL emission at 1.23 μm.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Note that Bi atoms tend to segregate during growth of GaAsBi and will then incorporate into the (Al)GaAs barrier, therefore increasing the total strain energy and altering the total thickness of the active layer [23]. Here we demonstrate that the growth of GaAsBi/ GaAs MQWs using a two-substrate-temperature (TST) technique during MBE growth, where the GaAs layer is grown at a higher temperature than the GaAsBi layer to sig-nificantlyreduce Bi segregation [22,24]. The material grown using the TST approach is of high optical device quality as demonstrated by the successful realization of p-i-n diode structures based on GaAs 0.96 Bi 0.04 /GaAs MQWs with RT EL emission at 1.23 μm.…”
Section: Introductionmentioning
confidence: 80%
“…The substrate temperature of the GaAsBi layers, T , GaAsBi was 350 °C and that of the GaAs layers, T , GaAs 550 °C. The growth was interrupted for 5 min at the GaAs on GaAsBi interface to increase the substrate temperature from T GaAsBi to T GaAs while the growth was interrupted for 10 min at the GaAsBi-on-GaAs interface in order to reduce the growth temperature of the Bi-containing layer [22,24,25]. The substrate temperature was measured by a pyrometer calibrated using both InSb and Al melting points.…”
Section: Methodsmentioning
confidence: 99%
“…The conduction band offset equal to nearly 40 % of the energy band gap difference of GaAs and GaAsBi has been predicted theoretically in [ 79 ]; the value of 23% was found from the X-ray photoemission [ 80 ] and as high as 48% from the photoreflectance studies [ 81 ]. Additional uncertainty was introduced by the photoluminescence investigations from multiple quantum wells in ref [ 82 ]. Authors concluded that the arrangement of bands in the GaAsBi-GaAs heterojunction corresponds to the staggered (type-II) and not to the straddling (type-I) variant.…”
Section: Heterostructure Band Offsetsmentioning
confidence: 99%
“…The quality of GaAsBi QW is also dependent on the Bi composition and the growth temperature. For particular growth condition, the flux has to be precisely controlled because a shortage of Bi can result in a surface roughness whereas a Bi excess causes formation of Bi droplet [23,27,37]. All these factors favor lifting the parity restrictions for the 1e→2hh transitions in our dilute bismides.…”
Section: A) Dependence On Excitation Intensitymentioning
confidence: 99%
“…These and other applications have stimulated extensive recent studies of dilute bismides [19][20][21][22][23][24][25][26][27][28][29][30]. They could make use of high quality GaAs 1-x Bi x /GaAs separate confinement heterostructures [14,31,32] and multiple quantum wells [31,[33][34][35][36][37] in the active regions. In previous studies, we investigated the effects of AlGaAs cladding on the luminescent properties of GaAs/GaAs 1-x Bi x /GaAs heterostructures [32] where the PL was demonstrated to be substantially more thermally stable PL than an isolated single quantum well (SQW).In this work, we investigate the optical properties of molecular beam epitaxy grown double GaAsBi/GaAs QWs.…”
Section: Introductionmentioning
confidence: 99%